Domperidone use and risk of primary liver cancer in the Clinical Practice Research Datalink. (August 2018) - Thistle, Jake E.; Petrick, Jessica L.; Yang, Baiyu; Bradley, Marie C.; Graubard, Barry I.; McGlynn, Katherine A.
Highlights: Overall, the study found no association between domperidone use and liver cancer. Among women there was an elevated risk among those who received the greatest number of prescriptions. These results do not support the hypothesis that increasing prolactin level via domperidone is likely to decrease the risk of liver cancer. The indication of increased risk among women warrants further study. Abstract: Background: Pronounced sex-disparity in liver cancer suggests a role for hormones, one of which could be prolactin. Stimulation of prolactin production in mice via domperidone has been reported to decrease hepatocarcinogenesis, thus may have chemopreventive potential. To study the effect of domperidone in humans, a large medical records study was conducted. Methods: Based in the Clinical Practice Research Datalink, 1921 liver cancer cases and 7681 controls were identified. Conditional logistic regression was employed to estimate odds ratios (OR) and 95% confidence intervals (CI). Domperidone use was analyzed overall, and by number of prescriptions and cumulative dose. Results: Comparing ever- versus never-use, there was no association between domperidone and liver cancer among men (OR = 1.06, 95% CI: 0.76–1.48) or women (OR = 1.21, 95% CI: 0.82–1.76). Among men, there was no association with dose or number of prescriptions, while among women who received the highest doses (OR2700 mg vs. 0 mg  = 2.52, 95% CI: 1.18–5.41, p-trend  = 0.02) and greatest number of prescriptions (OR≥11 Rx vs. 0 Rx  = 3.17, 95% CI: 1.07–9.40, p-trend  = 0.02) there was a significantly increased risk, although there was no evidence of heterogeneity in the results by gender. Conclusion: Domperidone use was not associated with decreased liver cancer risk among all study participants. Among women, an increased risk at highest levels of exposure warrants further study.